Chemvilative: Enhancing Conceptual Understanding in Chemistry Through an Android-Based Virtual Laboratory - Elvi Raziana; Sri Yamtinah; Djono (Jurnal Penelitian Pendidikan IPA, 2025)
Chemistry education often faces challenges due to limited access to laboratory facilities, particularly in abstract topics like buffer solutions, where hands-on experimentation is critical for conceptual understanding. This research aims to develop and evaluate the effectiveness of Chemvilative, an Android-based interactive virtual laboratory designed to address these challenges by providing accessible, engaging, and hypothesis-driven simulations for teaching buffer solutions in high school chemistry. The study addresses challenges related to limited laboratory facilities and the need for more accessible and engaging learning tools. The study used a Research and Development (R&D) methodology based on the ADDIE model, which guided the process from analysis, design, development, implementation, and evaluation. Chemvilative was validated by chemistry experts, teachers, and students. Feasibility was assessed via a 4-point Likert scale questionnaire (material and media), while effectiveness was measured through pre-test/post-test comparisons (N = 120 students). Results showed that Chemvilative significantly improved students' conceptual understanding compared to traditional teaching methods. There was a 15% increase in post-test scores. The virtual laboratory was rated as highly feasible. It provides clear visualizations and interactive simulations that enhance both learning motivation and comprehension. These findings suggest that Chemvilative is a practical and effective alternative for chemistry learning, especially in environments with limited laboratory resources. Future research should expand Chemvilative to other chemistry topics and evaluate its scalability across diverse student populations.